InCl3-catalyzed 5-exo-dig cyclization/1, 6-conjugate addition of N-propargylamides with p-QMs to construct oxazole derivatives. Issue 9 (19th February 2020) - Nan, Guang-Ming; Li, Xue; Yao, Tian-Yu; Yan, Ting-Xun; Wen, Li-Rong; Li, Ming
Abstract : An InCl3 -catalyzed tandem intramolecular 5- exo-dig cyclization/1, 6-conjugate addition/aromatization of N -propargylamides with p -QMs to produce oxazoles tethering diarylmethane has been successfully developed. Abstract : An InCl3 -catalyzed atom-economic intramolecular 5- exo-dig cyclization/1, 6-conjugate addition/aromatization of N -propargylamides with p -QMs to produce oxazoles tethering diarylmethane has been successfully developed. InCl3 not only served as Lewis acid to catalyze the cyclization of propargylic amides but also activated the carbonyl of p -QMs to achieve the 1, 6-addition process in a one-pot manner. The reaction has attractive features, including mild reaction conditions, broad scope of substrates, good yields, and scalability.